Political Campaign Strategies in the Era of COVID-19 Pandemic: Candidate Experiences in the 2020 Surabaya City Regional Election - Ikfina, Muhammad Ulfi (ARISTO, 2024)
Amid the COVID-19 pandemic and being promoted only by minor political parties, it didn’t impede the mayoral pairing candidate Eri Cahyadi-Armuji from winning the 2020 Surabaya mayoral election. Hence, the purpose of this study is to explain the political campaign strategy carried out by Eri Cahyadi-Armuji using the perspective of the five functional stages of development theory. This study applied a qualitative method with a case study approach. The findings of this study showed that Eri Cahyadi-Armuji successfully implemented the five stages of political campaign, thus he could win the election. However, there was an interesting note at the identification stage where Eri Cahyadi-Armuji preferred to use the identity of a figure rather than slogans. This fact deviated from the theory, yet it was successfully implemented as a surefire strategy to attract voters. Thus, this notable finding may give a contribution in developing the theory of political campaign strategy.